Odpowiedzialność karna za popełnienie czynu zabronionego w stanie tak zwanej zawinionej niepoczytalności - Liszewska, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The aim of this article is to analyse the problem of the criminal liability of a perpetrator who, while committing an offence, was in the state of inebriation or intoxication as a cause of insanity. Although the regulation of this matter was introduced in Art. 31 § 3 of the Criminal Code, it should be re-examined in the light of the separation of intentionality or negligence and culpability in the Criminal Code of 1997. Traditionally, insanity was treated as an exonerating circumstance, although the legislator mentions the elements that characterise intentionality and negligence. That is why, firstly the relation between Art. 31 § 1 and Art. 9 of the Criminal Code should be examined. Taking under consideration the result of this analysis, the article presents evidence that in the light of Art. 31 § 3 of the Criminal Code, the perpetrator can be sentenced only for a negligent offence.
Keywords: szaleństwo; stan nietrzeźwości lub zatrucie; wina; umyślność; zaniedbanie